Assessing Supply Chain Management with Supply Chain Operation Reference: A Case Study at Mommy House - Medikano, Alsen; Lase, Putri Dewi Rolasni (Jurnal Sistem Teknik Industri, 2023)
MSME by Mommy House is a business engaged in manufacturing by producing a variety of healthy foods. West Java Province from 2019 the number of MSME engaged in the culinary increase form 1,985,763 units reaching 2,239,092 units at 2021. Management realizes that it’s necessary for using the Supply Chain Operations Reference approach and the Analytical Hierarchy Process (AHP) to gain certainty about Supply Chain Management (SCM) performance, in order to satisfy customer desires with quality products. The MSME by Mommy House SCM process consists of suppliers, manufacturers, distribution and customers with SCM flows in the form of material, financial and information. The performance weighting of SCM uses the AHP approach, with the calculation results on the core plan of 0.113, the core source of 0.299, the core process of 0.332, the core delivering of 0.223 and the core process returning of 0.032. Snorm De Boer normalization the lowest and the highest score is 75 and 100. The highest final value is the make process with a performance value of 29.155 and the smallest is the return process of 3.113. Total supply chain performance value is 75.108 which is in the range of 70 to 90 meaning a good performance indicator.